Review of Portable CT with Assessment of a Dedicated Head CT Scanner - Rumboldt, Z.; Huda, W.; All, J.W. (American Journal of Neuroradiology, 2009)
SUMMARY: This article reviews a number of portable CT scanners for clinical imaging. These include the CereTom, Tomoscan, xCAT ENT, and OTOscan. The Tomoscan scanner consists of a gantry with multisection detectors and a detachable table. It can perform a full-body scanning, or the gantry can be used without the table to scan the head. The xCAT ENT is a conebeam CT scanner that is intended for intraoperative scanning of cranial bones and sinuses. The OTOscan is a multisection CT scanner intended for imaging in ear, nose, and throat settings and can be used to assess bone and soft tissue of the head. We also specifically evaluated the technical and clinical performance of the CereTom, a scanner designed specifically for neuroradiologic head imaging. The contrast performance of this scanner permitted the detection of 4-mm low-contrast lesions, and the limiting spatial resolution was 7 line pairs per centimeter. The measured volume of the CT dose index (CTDIvol) for a standard head CT scan was 41 mGy (120 kV/14 mAs). All clinical images were of diagnostic quality, and the average patient effective dose was 1.7 mSv. We conclude that the CereTom portable CT scanner generates satisfactory clinical images at acceptable patient doses.